Physical therapy in Down syndrome: systematic review and meta-analysis. - Ruiz González, Lorena; Lucena-Antón, David; Salazar, Alejandro; Martín-Valero, Rocío; Moral-Muñoz, José Antonio (Wiley, 2019)
Down syndrome is the most common chromosomal abnormality, with a worldwide incidence of around 0.1% in live births. It is related to several conditions in which the physical therapy could take action-preventing co-morbidities. This study aims to evaluate the effectiveness of physical therapy in Down syndrome, to know and compare the effectiveness of different physical therapy interventions in this population. Methods: A systematic review and a meta-analysis of randomised controlled trials were conducted. The search was performed during June 2018 in the following databases: PubMed, Web of Science, Physiotherapy Evidence Database and Scopus. The studies were selected using predefined inclusion and exclusion criteria. The Physiotherapy Evidence Database scale evaluated the quality of the methods used in the studies. Subsequently, the data were extracted, and statistical analysis was performed when possible. Results: A total of 27 articles were included, of which nine contributed information to the meta-analysis. Statistical analysis showed favourable results for the strength of upper and lower limbs [standardised mean difference (SMD) = 1.46; 95% confidence interval (CI): (0.77-2.15); and SMD = 2.04; 95% CI: (1.07-3.01)] and mediolateral oscillations of balance [SMD = -3.30; 95% CI: (-5.34 to -1.26)]. Conclusions: The results show the potential benefit of certain types of physical therapy interventions, specifically in strength and balance, in people with Down syndrome. There are still many aspects to clarify and new lines of research.
Política de acceso abierto tomada de: https://openpolicyfinder.jisc.ac.uk/id/publication/7080
Keywords: Síndrome de Down - Fisioterapia; Down syndrome; Intellectual disabilities; Meta-analysis; Physical therapy; Systematic review